A critical turn in numeracy education and practice - Geiger, Vince; Schmid, Mirjam (Frontiers in Education, 2024)
Research into the nature of numeracy and numeracy practice has typically been focused on the capabilities required to participate effectively within personal, civic, and work life. In this article, we document the development of numeracy theory and practice from a functional perspective through to a view that includes evaluative and decision-making capabilities now required for informed and responsible citizenship—a critical turn. We map this development through an audit of policy and curriculum documents in addition to published research, making connections to the ever-changing mathematical demands of society. These include new demands that require critical approaches to the deployment of numeracy capabilities. We argue that this turn to the critical is central to how citizens support their societies' responses to recent and intensifying disruptive phenomena such as COVID-19 and for ensuring equity, inclusiveness, and social justice remain a high priority in a rapidly changing world.